INTENTION TO MEDIATE THE RELATIONSHIP BETWEEN FINANCIAL ADVISORS' RECOMMENDATIONS AND STUDENT INVESTOR'S INVESTMENT DECISIONS - Alistraja Dison Silalahi ,; Sriwardany,; Shita Tiara,; Vivi Nadila,; Riska Ananda Putri, (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to find and analyze the effect of financial advisor recommendations on investment decisions of student investors in Medan with the intention of acting as a mediator. This research is a quantitative research with an explanatory research model, with primary data. Data collection techniques using a questionnaire. The data analysis technique is statistical analysis based on partial least squares. The results of the study found that the recommendations of financial advisors have a positive effect on investment decisions and the intention to mediate the effect of recommendations of financial advisors on investment decisions.